The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.3399/bjgp09x454007
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing European GPs' engagement in smoking cessation: a multi-country literature review

Abstract: Background: Smoking cessation advice by GPs is an effective and cost-effective intervention, but is not implemented as widely as it could be.  Aim: This wide-ranging Europe-wide literature review, part of the European Union (EU) PESCE (General Practitioners and the Economics of Smoking Cessation in Europe) project, explored the extent of GPs’ engagement in smoking cessation and the factors that influence their engagement.  Method: Two searches were conducted, one for grey literature, across all European count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
107
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(121 citation statements)
references
References 44 publications
8
107
0
5
Order By: Relevance
“…Only half recommend HCWs setting an example by not using tobacco, consistent with the findings from the treatment survey 5. Given the high reported rates of tobacco use by HCWs and students in some countries 7, 8, 9, 10, this remains a seriously neglected area.…”
Section: Discussionsupporting
confidence: 56%
“…Only half recommend HCWs setting an example by not using tobacco, consistent with the findings from the treatment survey 5. Given the high reported rates of tobacco use by HCWs and students in some countries 7, 8, 9, 10, this remains a seriously neglected area.…”
Section: Discussionsupporting
confidence: 56%
“…Studies conducted in Europe suggest that there is great diversity regarding GPs involvement in smoking cessation. This diversity is contingent on several factors, among which are the smoking behavior of the GPs, their attitudes towards smoking, reservations regarding inducing anxiety or guilt among pregnant women, but also self-confidence in providing cessation support 23 . A qualitative study involving family physicians (general practitioners) in Romania suggested that they generally feel untrained to offer smoking cessation support, emphasizing the need to integrate appropriate training in their professional development 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Other barriers to treatment included feeling discomfort when asking about tobacco use, holding the opinion that counseling was not an appropriate service for them to provide, dealing with competing priorities, and believing that patients would resist advice. General practitioners cite limited time, insufficient training, and lack of reimbursement for counseling, in addition to their self-perceived lack of knowledge and skill in dealing effectively with tobacco-dependent patients (143).…”
Section: What We Knowmentioning
confidence: 99%